1993
DOI: 10.1002/pola.1993.080311111
|View full text |Cite
|
Sign up to set email alerts
|

Confirmation of the presence of imine bonds in thermally cured polyimides

Abstract: SYNOPSISModel compounds for imines formed during the thermal curing of short chain polyimides have been synthesized and characterized. These compounds have imine bonds ( C = N ) formed by the nucleophilic attack of primary amines on imide carbonyls. The C = N stretching mode appears at 1649-1664 cm-' in the Raman and infrared spectra of these compounds and the band assigned to the carbonyl mode in an imide ring with an imine bond appears near 1740 cm-' . These compounds have been prepared and characterized to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 5 publications
2
22
0
Order By: Relevance
“…FTIR analysis confirmed the formation of imine in the heated mixtures. Similar imine bonds have been reported in Maillard-type reactions but it has never been used in pharmaceutical evaluation of the Maillard reaction (37,38). Developing the brown color development is a key factor of the Maillard reaction occurrence and is also in accordance with the modern techniques used in this study.…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…FTIR analysis confirmed the formation of imine in the heated mixtures. Similar imine bonds have been reported in Maillard-type reactions but it has never been used in pharmaceutical evaluation of the Maillard reaction (37,38). Developing the brown color development is a key factor of the Maillard reaction occurrence and is also in accordance with the modern techniques used in this study.…”
Section: Resultssupporting
confidence: 80%
“…Later at 2006, Namli et al followed the reaction process between benzaldehyde or salicylaldehyde and or 2-pyridinecarboxaldehyde with aniline and showed that resulting imine, shows a band in FTIR spectra at about 1,630 cm −1 (36). Other scientists have reported imine formation using FTIR spectroscopy with similar absorption bands (37,38). In the baclofen FTIR spectrum, the absorption band at about 1618 cm −1 is consistent with baclofen N-H bending vibration (Fig.…”
Section: Ftir Spectroscopymentioning
confidence: 88%
“…These wavelengths correspond to previously reported imide ring adsorptions 43–46. Complete cyclization was also evident by the lack of amide CO (1640 cm −1 ) and NH (1550 cm −1 ) peaks 47, 48.…”
Section: Resultssupporting
confidence: 89%
“…This side reaction could lead to branching and is promoted by a slight excess of basic groups and suppressed by a slight excess of acid groups. Saini et al [51] monitored amine terminated imide compounds by spectroscopy during heating. The appearance of a C --N absorption band confirmed that imide-imine conversion was occurring, which was predicted by a cross-link reaction mechanism involving the attack of terminal amino groups into imide carbonyl groups, with the resulting formation of imine.…”
Section: Thermal Cyclisationmentioning
confidence: 99%